Sustainable management and its impact on the development of the shrimp farming sector in the municipality of Guasave, Sinaloa, México. - Beltran, Lizbeth; Izaguirre-Díaz de León, Fridzia; López-Nevárez, Virginia; Portillo-Molina , Raul; Cordero-Ramírez , Jesús Damián; Peinado-Guevara, Victor Manuel (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The operative context in which companies are currently developing has changed, moving towards a sustainable environment; innovating and migrating towards a business model focused on sustainable management leads to a better economic, environmental and social performance of the organization. The objective of this research is to diagnose the administrative practices carried out in the shrimp farming sector of the municipality of Guasave, Sinaloa, in relation to sustainable management. The research is based on a qualitative approach, through a multi-case study strategy applicable to 6 companies located in the study area, with an exploratory, explanatory, documentary and non-experimental scope. Categories are defined according to the three main themes of the research: management factors in the organization, commercial management and sustainability management. The results show that there are notions of the importance of the management of factors aimed at sustainability, however, there is still a vague ecological awareness in the sector. It is concluded that it is essential for the shrimp farming sector to develop strategies and guidelines aimed at achieving sustainable management, which will allow meeting the requirements of national and international organizations and the creation of economic and non-economic value.